1963
DOI: 10.1172/jci104737
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Aldosterone, Cortisol, and Corticosterone Upon the Sodium and Potassium Content of Sheep's Parotid Saliva*

Abstract: Sodium depletion in the sheep results in a fall in parotid salivary sodium/potassium concentration ratio (Na/K) from a normal 25 to 40 (Na, 170 to 185 and K, 4 to 6 mEq per L) to as low 0.3 (Na, 40 and K, 133 mEq per L) (1, 2). Earlier work in this laboratory suggested that this reciprocal alteration in the concentration of salivary sodium and potassium was due predominantly to the simultaneous operation of 1) a fall in the salivary secretion rate and 2) an increase in the secretion of electrolyte-active adren… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
32
0

Year Published

1964
1964
2016
2016

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 67 publications
(33 citation statements)
references
References 21 publications
(24 reference statements)
1
32
0
Order By: Relevance
“…When animals are Na 1 -depleted (Scott, 1966) and under stimulation by aldosterone (Blair-West et al, 1963), both the salivary and the ruminal concentration of K 1 may rise to 100 mmol/l (Kay, 1960;Blair-West et al, 1963;Scott, 1966 and1967) Under these conditions, K 1 replaces (scarce) Na 1 in saliva, and not surprisingly, perhaps, a sizable reabsorption of K 1 from the rumen can be observed. Provided that ruminal K 1 is sufficiently high, a number of in vivo and in vitro studies have shown that preintestinal regions can contribute substantially to total recirculation of K 1 in the gastrointestinal tract of ruminants.…”
Section: Absorption Of Potassiummentioning
confidence: 99%
“…When animals are Na 1 -depleted (Scott, 1966) and under stimulation by aldosterone (Blair-West et al, 1963), both the salivary and the ruminal concentration of K 1 may rise to 100 mmol/l (Kay, 1960;Blair-West et al, 1963;Scott, 1966 and1967) Under these conditions, K 1 replaces (scarce) Na 1 in saliva, and not surprisingly, perhaps, a sizable reabsorption of K 1 from the rumen can be observed. Provided that ruminal K 1 is sufficiently high, a number of in vivo and in vitro studies have shown that preintestinal regions can contribute substantially to total recirculation of K 1 in the gastrointestinal tract of ruminants.…”
Section: Absorption Of Potassiummentioning
confidence: 99%
“…Clear evidence has now accumulated that a major factor causing a decrease in salivary Na: K ratio during salt depletion in sheep is increased secretion of aldosterone (Blair-West et al 1963, 1970a. In the present investigation, intravenous aldosterone administration in normal animals simulated the effect of sodium depletion as far as changes in saliva were concerned.…”
Section: Discussionmentioning
confidence: 81%
“…Furthermore, the control sodium-replete sheep submitted to the same series of ablations without exception had very low final outputs of aldosterone. In those sodiumdeficient sheep where the ablation caused a significant decrease of aldosterone secretion (e.g., Roland, Horst, and Archibald) the parotid salivary Na/K ratio rose, indicating a fall of aldosterone level in peripheral blood, whereas in those animals where the aldosterone remained high, the salivary Na/K ratio remained low, i.e., the chemical assay was consistent with this biological index of aldosterone secretion (29). \Ve are satisfied that radiochemical purity was achieved and that in the sodium-deficient animal the large aldosterone secretion assessed after these ablations was valid and not observed in the sodium-replete controls.…”
Section: Chemical Proceduresmentioning
confidence: 84%
“…With Croesus (Figure 1) and Ambrose (Figure 2), aldosterone remained high after all ablations, and correspondingly salivary Na/K ratio remained low throughout. With Ambrose the ratio was very low (0.02) and near the asymptote of the dose response curve relating aldosterone infusion rate to parotid salivary Na/K ratio (29). The fall of aldosterone secretion rate observed 2 hours after decerebration was followed 2 hours later by a rise of Na/K ratio.…”
Section: Chemical Proceduresmentioning
confidence: 86%
See 1 more Smart Citation